2020
DOI: 10.1016/j.scr.2020.102063
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cancer progression using human pluripotent stem cell-derived cells and organoids

Abstract: Conventional cancer cell lines and animal models have been mainstays of cancer research. More recently, human pluripotent stem cells (hPSCs) and hPSC-derived organoid technologies, together with genome engineering approaches, have provided a complementary platform to model cancer progression. Here, we review the application of these technologies in cancer modeling with respect to the cell-of-origin, cancer propagation, and metastasis. We further discuss the benefits and challenges accompanying the use of hPSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 156 publications
0
10
0
Order By: Relevance
“…In more detail, induced pluripotent stem cell–based cancer modeling can be used as follows ( 145 ): (I) genetic alterations can be engineered into normal human-induced pluripotent stem cells using transcription activator-like effector nucleases (TALENs) or CRISPR/Cas9 ( 146 ). These stem- derived cells with engineered cancer-associated mutations can be used to acquire the initial cancer molecular events to then emulate cancer progression ( 145 ). (II) Induced pluripotent stem cells can be used to reprogram patient-specific somatic cells with cancer predisposition syndromes such as Li–Fraumeni syndrome ( 147 ).…”
Section: Patient-derived Organoids From Cancer and Healthy Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In more detail, induced pluripotent stem cell–based cancer modeling can be used as follows ( 145 ): (I) genetic alterations can be engineered into normal human-induced pluripotent stem cells using transcription activator-like effector nucleases (TALENs) or CRISPR/Cas9 ( 146 ). These stem- derived cells with engineered cancer-associated mutations can be used to acquire the initial cancer molecular events to then emulate cancer progression ( 145 ). (II) Induced pluripotent stem cells can be used to reprogram patient-specific somatic cells with cancer predisposition syndromes such as Li–Fraumeni syndrome ( 147 ).…”
Section: Patient-derived Organoids From Cancer and Healthy Stem Cellsmentioning
confidence: 99%
“…(II) Induced pluripotent stem cells can be used to reprogram patient-specific somatic cells with cancer predisposition syndromes such as Li–Fraumeni syndrome ( 147 ). (III) Induced pluripotent stem cells can be engineered as cancer-specific cells by targeting tumor suppressors such as SMAD4, Rb/P16, BRCA1, CDKN1A, and CDKN2A ( 145 ). The previously mentioned stem cell strategies may help advance PDO research on H&N cancer.…”
Section: Patient-derived Organoids From Cancer and Healthy Stem Cellsmentioning
confidence: 99%
“…Researchers have found that 3D models are particularly successful in modeling the lineage progression, cellular heterogeneity and invasive potential of these devastating cancers (see Luo and Li, 2021 for a recent review). 3D modeling approaches for glioblastoma are ever evolving and have included organoids generated from primary patient samples or hPSC derivatives, and more recently bioprinted constructs that aim to more faithfully recapitulate multiple elements of the tumor tissue microenvironment (Gimple et al, 2019 ; Zhang et al, 2020 ; Stanković et al, 2021 ). There are two main approaches to 3D cancer modeling: creating a “tumorsphere” consisting of cancer cells to model growth, signaling and drug response (Lenin et al, 2021 ; Pinto et al, 2021 ) or co-culture of cancer cells with “normal” organoids to study invasion and tumor formation (Choe et al, 2020 ; Azzarelli et al, 2021 ).…”
Section: Complementing and Building On Animal Models With Human Stem Cell Modelsmentioning
confidence: 99%
“…12 As such, hiPSCs derived from healthy donors present an unlimited resource of cells to serve as receiver matrixes for genetic elements encoding for cancer-relevant transformations. Such healthy donorderived tumor models -herein referred to as hiPSC-oncogene models -manifest themselves as a sustainable alternative disease modeling strategy in the current cancer research community [13][14][15][16][17][18] complementing the portfolio of lab tools alongside the use of PD systems. It is speculated that iPSC models of cancer, derived through synthetic approaches or reprogramming of tumor cells, may be beneficial to homogeneously depict a cell of origin of cancers.…”
Section: Introductionmentioning
confidence: 99%